Philippine public administration, 1898-1968 an annotated bibliography - Ortiz, Edna P. (1972)
This is an annotated bibliography of documents, books, pamphlets, book chapters and periodical articles tracing the development of Philippine public administration covering the period 1898-1968. An interdisciplinary field of study, public administration embraces the whole area of man's effort to govern himself and thus includes materials on sociology, psychology, anthropology and other sciences relating to man's interaction with his fellowman.